2013
DOI: 10.1042/bj20121466
|View full text |Cite
|
Sign up to set email alerts
|

Prohepcidin binds to the HAMP promoter and autoregulates its own expression

Abstract: Hepcidin is the major regulatory peptide hormone of iron metabolism, encoded by the HAMP (hepcidin antimicrobial peptide) gene. Hepcidin is expressed mainly in hepatocytes, but is also found in the blood in both a mature and prohormone form. Although, the function of mature hepcidin and the regulation of the HAMP gene have been extensively studied, the intracellular localization and the fate of prohepcidin remains controversial. In the present study, we propose a novel role for prohepcidin in the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Prohepcidin was found to specifically bind to the STAT3 site in the promoter of the HAMP gene, thus suggesting that prohepcidin affects the expression of its own gene, indicating an autoregulatory loop of hepcidin gene expression [24]. Using liquid chromatography in combination with high-resolution mass spectrometry, we and others were able to identify new forms of hepcidin in human plasma or serum samples [59,60].…”
Section: Hepcidin; the Queen Of ‘Ironomics'mentioning
confidence: 99%
See 1 more Smart Citation
“…Prohepcidin was found to specifically bind to the STAT3 site in the promoter of the HAMP gene, thus suggesting that prohepcidin affects the expression of its own gene, indicating an autoregulatory loop of hepcidin gene expression [24]. Using liquid chromatography in combination with high-resolution mass spectrometry, we and others were able to identify new forms of hepcidin in human plasma or serum samples [59,60].…”
Section: Hepcidin; the Queen Of ‘Ironomics'mentioning
confidence: 99%
“…1). The peptide is encoded by the HAMP gene [24] which codes for the precursor protein pro-hepcidin which then is cleaved into the active hepcidin. Many mechanisms involved in the regulation of hepcidin synthesis in relation to iron have been elucidated [25,26,27].…”
Section: Hepcidin; the Queen Of ‘Ironomics'mentioning
confidence: 99%
“…A study by Pandur et al [58] indicated that hepcidin plays a direct role in its own regulation, with prohepcidin, the precursor of hepcidin, acting via a novel negative feedback mechanism to downregulate HAMP activity. Binding of prohepcidin to the HAMP promoter STAT3 downregulates HAMP transcription but this is offset by α-1 antitrypsin, which binds to prohepcidin and inhibits its autoregulatory activity.…”
Section: Hepcidin Regulationmentioning
confidence: 99%
“…Most of the research about hepcidin has focussed on this active form, and not much was known about the role of prohecidin, if any, in iron metabolism. A recent study examining the role of prohepcidin suggested that it is involved in feedback control of hepcidin transcription; using a variety of assays it was shown that prohepcidin binds directly to the STAT3 binding site in the HAMP promoter (Pandur et al, 2013). Prohepcidin also localised to the nucleus and cytoplasm as well.…”
Section: Autoregulation By Prohecidinmentioning
confidence: 99%